Epitaxial growth of complex metal oxides - Koster, Gertjan, 1971-; Huijben, M. (Mark); Rijnders, Guus (Woodhead Publishing series in electronic and optical materials., 2022)
Epitaxial Growth of Complex Metal Oxides, Second Edition reviews techniques and recent developments in the fabrication quality of complex metal oxides, which are facilitating advances in electronic, magnetic and optical applications. Sections review the key techniques involved in the epitaxial growth of complex metal oxides and explore the effects of strain and stoichiometry on crystal structure and related properties in thin film oxides. Finally, the book concludes by discussing selected examples of important applications of complex metal oxide thin films, including optoelectronics, batteries, spintronics and neuromorphic applications. This new edition has been fully updated, with brand new chapters on topics such as atomic layer deposition, interfaces, STEM-EELs, and the epitaxial growth of multiferroics, ferroelectrics and nanocomposites.